2017
DOI: 10.1093/brain/awx217
|View full text |Cite
|
Sign up to set email alerts
|

Distinct spatiotemporal patterns of neuronal functional connectivity in primary progressive aphasia variants

Abstract: Primary progressive aphasia is a syndrome characterized by progressive loss of language abilities with three main phenotypic clinical presentations, including logopenic, non-fluent/agrammatic, and semantic variants. Previous imaging studies have shown unique anatomic impacts within language networks in each variant. However, direct measures of spontaneous neuronal activity and functional integrity of these impacted neural networks in primary progressive aphasia are lacking. The aim of this study was to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
67
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 72 publications
9
67
0
Order By: Relevance
“…Thus, areas that are functionally connected to regions of atrophy are likely also to show abnormal responses in the early stages of degeneration as the proteinopathy begins to affect them. Recent studies of neural activity in PPA using resting-state recordings have also shown that functional abnormalities exist in widespread networks beyond the zones of atrophy ( Bonakdarpour et al, 2017 ; Ranasinghe et al, 2017 ), and that functional connectivity in the healthy brain predicts the spread of atrophy in PPA ( Mandelli et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, areas that are functionally connected to regions of atrophy are likely also to show abnormal responses in the early stages of degeneration as the proteinopathy begins to affect them. Recent studies of neural activity in PPA using resting-state recordings have also shown that functional abnormalities exist in widespread networks beyond the zones of atrophy ( Bonakdarpour et al, 2017 ; Ranasinghe et al, 2017 ), and that functional connectivity in the healthy brain predicts the spread of atrophy in PPA ( Mandelli et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may help to clarify the nature of the signal, and may also provide critical evidence regarding the brain basis of stroke recovery, the basis of day-to-day fluctuations in behavioral performance, and also the basis of behavioral response to neurorehabilitation, medications, and neuromodulation. Finally, efforts have been made to use resting BOLD data to identify functional changes in several clinical populations, often examining changes in resting state connectivity (He et al, 2007;Liu et al, 2018;Nair et al, 2015;Park et al, 2018;Ranasinghe et al, 2017); likewise, the technique described here may be applied to other populations without gross anatomical damage to identify functional anomalies in individuals with neurodegenerative disorders, psychiatric disorders, developmental disorders, or other clinical populations. Beyond clinical applications, this technique could also potentially be used to measure development or skill acquisition (e.g., literacy) or examine any source of individual difference in brain function, such as sensory experience (e.g., blind or deaf populations), multilingualism, or socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…MEG has only been deployed recently to investigate PPA (e.g., Kielar et al, 2018), but has already shown its potential as a tool to study the neurophysiological signatures of network-level alterations due to neurodegenerative disorders. It can be instrumental in identifying syndromespecific changes in the spectral properties of oscillatory responses (Ranasinghe et al, 2017;Sami et al, 2018). As suggested by task-free fMRI evidence, these functional alterations might precede structural ones and may be key for early diagnosis (Bonakdarpour et al, 2017).…”
Section: The Latency Of the Dorsal Activation Indicates Slow Serial mentioning
confidence: 99%